Comparative Study of the Ḥadīth: “God Is Inside Objects…” (Arabic: داخل فی الأشیاء) and the Philosophical Rule of Indivisible Entity (Arabic: بسیط الحقیقة) from the Perspective of Transcendent Theosophy and Mysticism - Ramin Golmakani; Sayyid Ali Delbari; Muhammad Gholami Jami (آموزه‌‌های فلسفه اسلامي, 2023)
The ability of deduction, explanation, inference and defending of some knowledge is axiomatic and undeniable. A narrative (ḥadīth) about the relationship of the Truth (Arabic: حقّ تعالی) and things is narrated in the narrative, theological, philosophical and mystical books narrated by Imam Ali (as) that God “is not inside objects; not like entering of an object in another object and He is outside objects without exiting of object from an object” and without doubt, this word is not of the kind of mystery and has an understandable meaning for the audience. The question is what does it mean by God being inside or outside of things? Is it possible to interpret it using philosophical fundamentals or should it be left to understand it in the time of the presence and encounter with Maʿṣūm (Arabic: معصوم, the Infallible) In this article, we have mentioned while implicative and document reviewing of Ḥadīth and stating different words and interpretations, the evidence of the verses and traditions and we have shown that a reasonable meaning from this ḥadīth can be presented by explaining the philosophical rule of: “«بسیط الحقیقة کلّ الأشیاء ولیس بشیء منها»” [Indivisible Entity or God (Arabic: بسیط الحقیقة) is all things and it is none of them] and show that God is Indivisible Entity and He is the Infinite that pervasive of all their objects and perfections and none of them is outside of Him and none of the limits of possibility can be found in Him.